A atividade mineira em Ametista do Sul/RS e a incidência de silicose em garimpeiros - Pagnossin, Elaine Medianeira (2007)
The municipal district of Ametista do Sul, located in the north of the state of Rio Grande do Sul is eminent in the production of amethysts which occur in geodos in the interior of spills of basalt of Formação Serra Geral. The extraction of amethyst is made in large horizontal profundities in underground galleries. The process of plow involves tasks such as the perforation of the rock which is made in a dry way and the use of explosives, both of them create mineral dust with silica (SiO2) which remains in suspension a lot of time inside the gallery, causing the inhalation and the risk of developing lung diseases, among them the silicosis, a incidence of silicosis in prospectors of Ametista do Sul. In order to do that, it was carried out a survey in medical report, home visits to the prospectors that were out of work. Relevant information was selected in the medical reports, such as age, occupation time, smoker or non-smoker, diagnosis of the illness, incident symptoms and clinical exams carried out. The results found in the medical reports showed that 44% have silicosis and 56% do not have the diagnosis of the disease but present the symptoms of it. During the home visits, it was found 23 prospectors away from work due to the high evolution of silicosis. In the interviews with the prospectors, the results showed that 78% do not have silicosis, 11% have the disease and 11% do not know whether they have the disease because they have not done the exam for the diagnosis, or those who did the exam have not gotten the medical diagnosis yet. In this context, it was checked that it is necessary changes in the technique of work especially in the perforation method through the use of water as well as improvements in the process of ventilation that is insufficient; in addition to better inspection and control in the use of toxic components of explosives which also affect the respiratory ways of the prospectors.